Diversity of Bentos in Fresh Water and Branches Water in The Kambu River, Lalolara District - Suharno, Suharno (Universitas Sembilanbelas November Kolaka, 2022)
Benthic animals are often used as biological indicators of water quality because benthos have relatively fixed habitats, with such characteristics, changes in water quality and the substrate where they live greatly affect their composition. Benthic density is also strongly influenced by its tolerance and sensitivity to environmental changes. The purpose of this research is to determine the type of macrozoobenthos in the Lalolara River, Kambu District, Kendari City. This type of research is descriptive research with observational sampling techniques. The observation technique used is to go directly to the deep field observation and sampling of the flow of the Lalolara River. The river is about 20 m wide meter is divided into 20 observation points. Sampling was carried out on each line transect where each transect consisted of 4 plots measuring 30 x 30 cm. The results showed that there were six types of benthos found in the river Lalolara namely: Tarebia granifer, Pleurocera acuta, Medulia carinata, Planobula armigera, Viviparus interitextus, Parapholyx effusa. Based on the results of the study, it appears that the species Tarebia granifer dominates both forms of the substrate. Also from the observations, the comparison between substrates shows that the sandy substrate has a large number of individuals with a higher diversity than the silty substrateÂ Keywords: Diversity, BentosÂ